Unveiling the technology acceptance model: a systematic review of evolution, impact across industries and future directions - Du, Shengwei; Hashim, Norliana; Kamarudin, Syafila (Elite Scientific Publications, 2024)
With the growth of contemporary information technology and scientific research, people’s lives are becoming increasingly inseparable from information technology. Since people can obtain information through technology, researchers have been committed to studying the relationship between users and technology. Since the mid-20th century, researchers have designed many theoretical models. However, among these models, the most frequently used by researchers is the Technology Acceptance Model (TAM). Based on this, this paper adopts a systematic literature review method and uses Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) to collect, analyze, summarize and obtain results. This paper selects the Science Direct and ProQuest databases, with a time limit of 2015–2024, and selects 38 papers according to the screening criteria. This paper analyzes TAM’s research trends, origins, development, research fields, and future development directions. It is pointed out that Perceived Ease of Use, Perceived Usefulness, attitude toward using, behavior intention to use, and subject normal are important reasons that affect users’ use of technology. Moreover, behavioral intention to use and attitude toward using play a crucial role as mediators in the connection between users’ perceived ease of use, perceived usefulness, and actual use behavior. This paper can provide valuable data and suggestions for future researchers studying TAM. This paper can also prompt the government and related technology companies to understand why users use technology. In particular, technology designers can grasp why users use technology, encourage users to use information technology, and increase user stickiness.